Constructive Parameters of Earthquake Unit Before Sowing - Kamaljon Mukhamadsadikov; Bobojon Ortiqaliyev (Genius Journals, 2022)
This article presents the results of theoretical studies to determine the force acting on the working body of the pre-sowing leveller, as well as the resistance force appearing from the soil dragging prism when moving in front of the working body of the leveller and the installation angle, height of the working body of the pre-sowing leveller.
Keywords: Leveller; installation; height; deformation